Dimethyl fumarate alleviates allergic asthma by strengthening the Nrf2 signaling pathway in regulatory T cells - Cen, Yanhong; Li, Fangfang; Li, Yikui; Zhang, Kaimin; Riaz, Farooq; Zhao, Kuaile; Wei, Ping; Pan, Fan (Frontiers in Immunology, 2024)
Allergic asthma is a widely prevalent inflammatory condition affecting people across the globe. T cells and their secretory cytokines are central to the pathogenesis of allergic asthma. Here, we have evaluated the anti-inflammatory impact of dimethyl fumarate (DMF) in allergic asthma with more focus on determining its effect on T cell responses in allergic asthma. By utilizing the ovalbumin (OVA)-induced allergic asthma model, we observed that DMF administration reduced the allergic asthma symptoms and IgE levels in the OVA-induced mice model. Histopathological analysis showed that DMF treatment in an OVA-induced animal model eased the inflammation in the nasal and bronchial tissues, with a particular decrease in the infiltration of immune cells. Additionally, RT-qPCR analysis exhibited that treatment of DMF in an OVA-induced model reduced the expression of inflammatory cytokine (IL4, IL13, and IL17) while augmenting anti-inflammatory IL10 and Foxp3 (forkhead box protein 3). Mechanistically, we found that DMF increased the expression of Foxp3 by exacerbating the expression of nuclear factor E2-related factor 2 (Nrf2), and the in-vitro activation of Foxp3+ Tregs leads to an escalated expression of Nrf2. Notably, CD4-specific Nrf2 deletion intensified the allergic asthma symptoms and reduced the in-vitro iTreg differentiation. Meanwhile, DMF failed to exert protective effects on OVA-induced allergic asthma in CD4-specific Nrf2 knock-out mice. Overall, our study illustrates that DMF enhances Nrf2 signaling in T cells to assist the differentiation of Tregs, which could improve the anti-inflammatory immune response in allergic asthma.